The Role of Synthesis Methods of Ceria-Based Catalysts in Soot Combustion - Gabriela Grzybek; Andrzej Wójtowicz; Piotr Legutko; Magdalena Greluk; Grzegorz Słowik; Andrzej Sienkiewicz; Andrzej Adamski; Andrzej Kotarba (Molecules)
The removal of soot particles via high-performance catalysts is a critical area of research due to the growing concern regarding air pollution. Among various potential catalysts suitable for soot oxidation, cerium oxide-based materials have shown considerable promise. In this study, CeO2 samples obtained using a range of preparation methods (including hydrothermal synthesis (HT), sonochemical synthesis (SC), and hard template synthesis (TS)) were tested in soot combustion. They were compared to commercially available material (COM). All synthesized ceria catalysts were thoroughly characterized using XRD, RS, UV/Vis-DR, XPS, H2-TPR, SEM, and TEM techniques. As confirmed in the current study, every tested ceria sample can be used as an effective soot oxidation catalyst, with a temperature of 50% soot conversion not exceeding 400 °C in a tight contact mode. A strong correlation was observed between the catalysts’ Ce3+ concentration and activity, with higher Ce3+ levels leading to improved performance. These findings underscore the importance of synthesis in optimizing ceria-based catalysts for environmental applications.